Intradialytic hypotension frequency is reduced by levocarnitine supplementation - Stefano Aterini; Anna Maria Ciciani; Franco Bergesio; Lorenzo Aterini; Barbara Vadalà; Marco Gallo (AboutScience Srl, 2022)
Introduction: Intradialytic hypotension (IDH) is a frequent complication of hemodialysis. IDH causes intradialytic discomfort and subclinical ischemia, resulting in a higher rate of morbidity and mortality. Levocarnitine (LC) administration has been suggested for the treatment of IDH, but conflicting reports about its efficacy have been published. We describe the effect of LC supplementation in patients experiencing recurrent IDH episodes, in spite of common strategies used to prevent it. Methods: Sixteen hemodialysis patients were studied. IDH was defined as a drop in systolic blood pressure ≥20 mmHg, with or without symptoms, prompting an intervention by the dialysis staff, such as reducing/stopping ultrafiltration rate and/or fluid administration. Blood pressure was recorded for 192 hemodialysis sessions, before LC supplementation. Thereafter LC (30 mg/kg dry weight) was administered at the beginning of each hemodialysis, registering blood pressure for 384 hemodialysis treatments. The difference between the predialysis systolic blood pressure and the minimum systolic blood pressure of each hemodialysis was evaluated (∆SBP), before and after LC supplementation. Cardiac ejection fraction was also measured. Results: Predialysis and postdialysis systolic, diastolic, and mean arterial pressures did not differ before and after LC supplementation. Before LC supplementation, 36 episodes of IDH occurred (19%), while after LC supplementation, the IDH episodes were 29 during 384 hemodialysis sessions (8%; χ2 = 16.03; p = 0.0001). ∆SBP was lower after LC supplementation, even though the difference was not significant (p = 0.22). Conclusion: IDH frequency was significantly reduced by predialysis LC supplementation, which can be helpful for patients' well-being and reduction in IDH-associated risks.